Temporal analysis of natural variation for the rate of leaf production and its relationship with flowering initiation in Arabidopsis thaliana - Méndez-Vigo, Belén (Journal of experimental botany, 2010)
Vegetative growth and flowering initiation are two crucial developmental processes in the life cycle of annual plants that are closely associated. The timing of both processes affects several presumed adaptive traits, such as flowering time (FT), total leaf number (TLN), or the rate of leaf production (RLP). However, the interactions among these complex processes and traits, and their mechanistic bases, remain largely unknown. To determine the genetic relationships between them, the natural genetic variation between A. thaliana accessions Fei-0 and Ler has been studied using a new population of 222 LerxFei-0 recombinant inbred lines. Temporal analysis of the parental development under a short day photoperiod distinguishes two vegetative phases differing in their RLP. QTL mapping of RLP in consecutive time intervals of vegetative development indicates that Ler/Fei-0 variation is caused by 10 loci whose small to moderate effects mainly display two different temporal patterns. Further comparative QTL analyses show that most of the genomic regions affecting FT or TLN also alter RLP. In addition, the partially independent genetic bases observed for FT and TLN appear determined by several genomic regions with two different patterns of phenotypic effects: regions with a larger effect on FT than TLN, and vice versa. The distinct temporal and pleiotropic patterns of QTL effects suggest that natural variation for flowering time is caused by different genetic mechanisms involved in vegetative and/or reproductive phase changes, most of them interacting with the control of leaf production rate. Thus, natural selection might contribute to maintain this genetic variation due to its phenotypic effects not only on the timing of flowering initiation but also on the rate of vegetative growth